2006
DOI: 10.1007/s10562-006-0194-8
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of diesel soot on mixed oxides derived from hydrotalcites

Abstract: MAlO (where M = Ni 2+ , Co 2+ and Cu 2+ ) mixed oxides derived from hydrotalcites and potassium-promoted MAlO catalysts (designated as K/MAlO; K: 5 wt.%) have been studied for diesel soot oxidation. The catalysts were characterized by XRD, N 2 adsorption, TPR, FT-IR and TPO techniques. The hydrotalcites calcined at 800°C have large surface areas in the range 17-88 m 2 / g and uniform mesoporous features, which resulted in high activity for diesel soot oxidation under the conditions of tight contact between soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Although numerous investigations on the soot combustion catalysts have been conducted and theoretical models for NOx storage have been developed [4][5][6][7][8][9], some problems still remain. Among them, the too high temperature of soot combustion and the relatively low NOx storage capacity (NSC) are the main aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous investigations on the soot combustion catalysts have been conducted and theoretical models for NOx storage have been developed [4][5][6][7][8][9], some problems still remain. Among them, the too high temperature of soot combustion and the relatively low NOx storage capacity (NSC) are the main aspects.…”
Section: Introductionmentioning
confidence: 99%
“…A promising process to meet this demand is the simultaneous catalytic removal of NO x and soot. 17 Previous studies have shown that the oxidation of soot and the reduction of nitrogen oxides can be achieved in the same reaction temperature range. In addition, the existence of nitrogen oxides can lower the activation energy of soot combustion.…”
Section: Yanshan Gaomentioning
confidence: 99%
“…In the process of catalytic oxidation of soot, a high activity of the catalyst is a key factor. To date, various soot oxidation catalysts such as alkali metal titanates, 9 alkali metal zirconates, 10 alkali modified aluminosilicates, 11,12 transition metal oxides, [13][14][15][16] and rare earth-based catalysts 17 have been reported.…”
Section: Yanshan Gaomentioning
confidence: 99%
See 1 more Smart Citation
“…LDHs represent suitable candidates for the simultaneous removal of NO x and soot, as summarized in Table 1. Being their catalytic activity strongly related to the nature of metals, their amount and calcination temperature, different formulations have been proposed and between them copper-, cobalt-, or nickel-based oxides have demonstrated high activity in oxidation reactions [19], like soot combustion. Moreover, it is well known that the addition of alkali oxides, and in particular K can further improve their activities favoring the reaction through the formation of low melting point compounds [20], or of eutectics with other catalyst components, thus improving the surface mobility of the active species [12,13,21] and hence favoring the soot-catalyst contact, which has been claimed as a key factor in the soot oxidation process.…”
Section: Hydrotalcites and Mixed Metal Oxides Catalystsmentioning
confidence: 99%